One aspect of the role of ICTs in a mountain community : a case study of Kamiyama, Japan - Kenji Hashimoto (Netcom)
This paper explains the satellite office project in Kamiyama Town, which is located in a peripheral mountain area with an aging population in the Myōzai District of Tokushima Prefecture. Kamiyama has leveraged broadband to attract ICT industry from urban areas, create employment and encourage young workers to move to the town. Several key factors contributed to success in Kamiyama, including the capabilities of innovator companies, the capacity of the local host organization ‘Green Valley’, the existence of a horizontal network among companies that have moved to the area, and convenient access to home offices and markets in Tokyo and Osaka. On the other hand, a limited supply of old houses suitable for use as satellite offices and the cost of transportation to major cities are both significant barriers to the revitalization of this peripheral mountain village.